Выбор метода терапии у женщин с эндокринным бесплодием на фоне гиперпролактинемии - Кузьмина, И.Ю.; Липко, О.П.; Пасиешвили, Н.М.; Ткачева, О.В. (Таврический медико-биологический вестник, 2012)
Проведено лікування 46 пацієнток з гіперпролактинемією непухлинного ґенеза й первинною
безплідністю. Застосування агоністів дофаміна разом із кріоконсервованою сироваткою кордової крові
людини (КСККЛ) сприяє корекції гормонального статусу, нормалізації овуляції й менструального циклу у
пацієнток з ендокринною безплідністю. Treatment of 46 patients with hyperprolactinemia not tumoral genesis and primary barrenness is lead. It
is shown, that application of agonists of Dofaminum together with Cryopreservation of Serum of Cord Blood of
Human (СSCBH) promotes correction of the hormonal status, normalization of ovulation and menstrual cycle at
patients with endocrine infertility.